2020
DOI: 10.1039/c9ra07874f
|View full text |Cite
|
Sign up to set email alerts
|

Pulse electromagnetic fields enhance the repair of rabbit articular cartilage defects with magnetic nano-hydrogel

Abstract: Pulsed electromagnetic fields combined with magnetic nano-hydrogel can promote bone marrow mesenchymal stem cells to repair rabbit articular cartilage defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 33 publications
0
22
0
1
Order By: Relevance
“…IONPs physically coated on scaffolds might leak into the surrounding environment, which would weaken the inductive coupling magnetic effect. One solution is to chemically connect the embedded IONPs to the hydrogel so that they are less likely to diffuse into the surrounding environment and be ingested by surrounding cells ( Huang et al., 2020 ).…”
Section: Classification Of Nanocomposite Hydrogelsmentioning
confidence: 99%
“…IONPs physically coated on scaffolds might leak into the surrounding environment, which would weaken the inductive coupling magnetic effect. One solution is to chemically connect the embedded IONPs to the hydrogel so that they are less likely to diffuse into the surrounding environment and be ingested by surrounding cells ( Huang et al., 2020 ).…”
Section: Classification Of Nanocomposite Hydrogelsmentioning
confidence: 99%
“…In this study, we showed that MF exposure influences the cytoskeletal fiber organization. GAG deposition in magnetically stimulated ADSC-MNP was almost 5 times higher compared to non-loaded WJMSC, pointing to a possible modality for manipulating ADSC for improved chondrogenic conversion in vitro and, possibly, future methods for improving cartilage-repair pulsed magnetic field exposure (PEMF) of BM-ADSC in combination with magnetic hydrogels which were shown to increase repair in rabbit model of cartilage defects ( Huang et al, 2019 ). Further studies are needed to more precisely clarify the molecular mechanism governing the correlation between MNP positioning, MF exposure and increased chondrogenesis in ADSC.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, carboxylated cellulose nanocrystals (cCNCs) were prepared using ammonium persulfate as hydrogel inks, and stable cell-free and cell-loaded hydrogel inks with the best physicochemical properties and biocompatibility were developed [ 7 ]. We also used magnetic nanoparticles (Fe 2 O 3 ) as a bioink to generation magnetic nanocomposite hydrogel for cartilage tissue engineering [ 8 , 9 , 10 , 11 , 12 ].…”
Section: Bioinks For 3d Bioprintingmentioning
confidence: 99%